PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. FIDERAL INTERNATIONAL FINANCE MAKASSAR - Megawhati Artiyany; Andi Nonong Sunrawali (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to determine the effect of leadership, motivation, and job satisfaction on employee performance at PT. Fideral International Finance Makassar. Sources of data in this study are primary data and secondary data as well as data collection methods with questionnaires. The sample in this study was 82 people using a saturated sample. The data analysis method used was simple linear regression analysis and multiple linear regression. The results showed that leadership, motivation, and job satisfaction had a positive and significant effect on employee performance at PT. Fideral International Finance Makassar.